Resposta da cultura do pimentão fertirrigado no sistema de gotejamento com doses de nitrogênio e potássio em ambiente protegido - Lorenzoni, Marcelo Zolin (2016)
The sweet pepper crop is among the ten most economically important vegetable in Brazil. In greenhouses is one of five crops with larger area, both in Brazil and in several countries due to high productivity and fruit quality under these conditions. To ensure these benefits it is necessary to adapt the management to the protected environment, particularly regarding to water and nutritional supplementation. This study aimed to investigate the effects of fertigation management with the application of nitrogen and potassium, in growth and development and yield of sweet pepper. The experiment was carried out in a greenhouse situated in Irrigation Technical Center (CTI), at State University of Maringá, in Maringá - PR. Plants were grown in 25 liters pots using a randomized design with factorial scheme (4x4) with four replications. The treatments were formed through the combination of four nitrogen doses (0, 73.4, 146.8 and 293.6 kg ha-1), and four doses of K (0, 53.3, 106.7 and 213 4 kg ha-1). The fertilizers used were urea and potassium chloride as sources of N and K, respectively. The parameters evaluated were plant height, stem diameter, leaf area, dry weight of leaf, stem, root and total, production and number of commercial and non-commercial fruits. Data were subjected to variance analysis and later was carried out the regression study. The results showed that there was interaction in the application of N and K for stem diameter, leaf area, and dry weight of stem, leaf, root and total variables. Both productivity and number of commercial fruits there was interaction at the application rates of N and K fertigation with quadratic model adjustement both variables. The highest yield obtained in this study was 1882 g plant-1 (31.34 t ha-1) for the doses of 155 kg ha-1 and 106.7 kg ha-1 to N and K, respectively.